MAKNA SEMIOTIKA KAMPANYE MODERASI BERAGAMA PADA MASYARAKAT MILENIAL MELALUI KOMIK-KARIKATUR KARYA ABDULLAH IBNU THALHAH - Alliyah Ismah; Fajar Ramadhan; Siti Nurul Handayani; Tafsir; Abdullah Ibnu Thalhah (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2024)
This article discusses the semiotic meaning of the campaign for religious moderation in millennial society in the cartoon comic by Abdullah Ibnu Thalhah. This caricature comic media was created to make it easier for millennial people to gain the important values ​​of religious moderation. Because it can be seen that currently there are many violent conflicts betwee religious communities, this occurs due to a lack of education among the religious communities themselves. This research using semiotic analysis is to understand how the message of moderation is conveyed, through analysis that identifies symbols, icons and indices used in caricature comics for understanding and reflection for millennial society on the values ​​of religious moderation. Through this semiotic analysis, millennials receive education on religious moderation in an easy and practical way. The research method uses a qualitative approach with Roland Barthes' semiotic analysis. This semiotic analysis aims to make it easier to understand how the message of religious moderation is conveyed through the images in the cartoon comics. The data collection methods used were interviews, documentation, and semiotic analysis in the caricature comics. Keyword: Religious Moderation, Semiotics, Comic-Caricatures